Structural evaluation and mechanical property of boron nitride fibers during melt‐drawn fabrication process. Issue 3 (18th January 2018) - Wang, Chonghai; Hong, Changqing; Yan, Liwen; Lin, Xue; Zhang, Mingxia; Wang, Jiazhi; Qu, Qiang
Abstract: Boron nitride (BN) fibers were fabricated on a large scale through the melt‐drawn technique from low‐cost boric acid, NH3, and N2 . Evolution of structure and properties of BN fibers during the fabrication process was studied by Fourier transform infrared (FT‐IR), X‐ray diffraction (XRD), scanning electron microscope (SEM), and X‐ray photoelectron spectroscopy (XPS). The mechanical properties of BN fibers were tested and analyzed. The results shown that both the mechanical properties and the crystallinity of BN fibers slightly increased with the temperature from 450 to 850°C, due to the combination of the fused‐B3 N3 . For BN fibers heat‐treated at 850 or 1000°C, the tensile strength (σ R ) and elastic modulus ( E ) were strongly increased because of the increase in crystallization of the BN phase. The meso‐hexagonal BN fibers with a diameter of 5.0 μm were fabricated at 1750°C, of which the tensile strength (σ R ) and elastic modulus ( E ) are 1200 MPa and 85 GPa, respectively. BN fibers with excellent mechanical properties and proper diameters were obtained by nitriding of green fibers during their conversion into ceramic.